2021
DOI: 10.1007/s00018-021-03873-z
|View full text |Cite
|
Sign up to set email alerts
|

The pre-metastatic niche in lymph nodes: formation and characteristics

Abstract: Lymph node metastasis is a crucial prognostic parameter in many different types of cancers and a gateway for further dissemination to distant organs. Prior to metastatic dissemination, the primary tumor prepares for the remodeling of the draining (sentinel) lymph node by secreting soluble factors or releasing extracellular vesicles that are transported by lymphatic vessels. These important changes occur before the appearance of the first metastatic cell and create what is known as a pre-metastatic niche giving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 179 publications
(249 reference statements)
2
65
0
Order By: Relevance
“…POSTN is an ECM protein, which plays a key role in tissue remodeling by interacting with various ECM proteins such as collagen, fibronectin and integrins [ 15 ]. POSTN is highly expressed in primary tumors and has been reported to be upregulated in lung and liver PM niche [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…POSTN is an ECM protein, which plays a key role in tissue remodeling by interacting with various ECM proteins such as collagen, fibronectin and integrins [ 15 ]. POSTN is highly expressed in primary tumors and has been reported to be upregulated in lung and liver PM niche [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment of specific cell types [ 11 ] and the remodeling of the extracellular matrix (ECM) are therefore seen as crucial events in PM elaboration. PM niches have been well described for lung, liver and bone [ 12 14 ], but far less for LNs [ 15 ]. Lymphatic vasculature remodeling (lymphangiogenesis) is a key step in the formation of a LN PM niche and is primarily driven by vascular endothelial growth factors (VEGF-A and VEGF-C) [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described by Yamakawa et al (2018) , tumor cells can induce lymphangiogenesis from local lymph nodes through pro-lymphangiogenic signaling, effectively creating a highway for lymphatic metastasis. For an expert review on the pre-metastatic niche and tumor signaling in regional lymph nodes, readers are referred to the review by Gillot et al (2021) . Through the secretion of VEGF-C and VEGF-D, tumors of the breast, lung, colon, prostate, and cervix promote the formation of tumor lymphatic networks that serve as routes for metastasis ( Detmar and Hirakawa, 2002 ; Kesler et al, 2013 ).…”
Section: Reflecting On Future Directionsmentioning
confidence: 99%
“…Recent studies have demonstrated that in the tumor-involved lymph nodes, a range of immune-suppressive cells and biological factors would be recruited or activated, which facilitated the survival and growth of metastatic tumor cells. The mechanisms include the decrease of CD8+ T cells, myeloid-derived suppressor cell (MDSC) expansion, and upregulation of regulatory T cells ( 24 27 ). However, the exact alterations of metastatic tumor cells from primary tumor cells remained unclear.…”
Section: Classical Immune Phenotype Alterations Of Metastatic Cells I...mentioning
confidence: 99%